Physical abuse of older people reported at the Institute of Forensic Medicine in Recife, Pernambuco State, Brazil A violência física contra a pessoa idosa revelada em serviço médico-legal, Recife, Pernambuco, Brasil - Marcella de Brito Abath; Márcia Carréra Campos Leal; Djalma Agripino de Melo Filho; Ana Paula de Oliveira Marques (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
This cross-sectional study aimed to determine the profile of physical abuse against older people who underwent forensic examination at the Institute of Forensic Medicine in Recife, Pernambuco State, Brazil. The cases, with data from 1,027 forensic reports, were described according to characteristics of the incident, victim, and aggressor. Most cases of violence were produced by mechanical energy, either with blunt objects or by empty-handed attack; the most common day of the week was Sunday, most frequently in the evening, and in the victim's home; typical cases involved mild injuries on more than one part of the victim's body. The majority of the victims were men, 60 to 69 years of age, brown (mixed-race), married or living with a partner, and retirees/pensioners. The majority of the aggressors were men, known to the victim, and attacking alone. The social transcendence of violence against older people clearly calls for investment in programs to deal with the problem in order to ensure better quality of life for the elderly. Conduziu-se um estudo transversal com o objetivo de determinar o perfil da violência física em idosos submetidos à perícia traumatológica, entre 2004 e 2007, no Instituto de Medicina Legal do Recife, Pernambuco, Brasil. Os casos, cujas informações procederam de 1.027 laudos, foram descritos segundo características do evento, da vítima e do agressor. Com maior freqüência, a violência foi produzida por energia mecânica, instrumento contundente e arma natural; ocorreu num domingo, turno noturno e residência da vítima; acometeu mais de uma parte do corpo e a lesão foi leve. Prevaleceram como vítimas os homens, com idade entre 60 e 69 anos, pardos, casados/união consensual e aposentados/pensionistas. A maioria dos agressores era homem, conhecido da vítima e a agrediu desacompanhado. A transcendência social do problema torna imperativo o investimento em programas para seu enfrentamento, possibilitando uma melhor qualidade de vida para o idoso.